Buffer stops behavior due to rail impact loads with LISA FEA - Aco Wahyudi Efendi; Chi Weijia (Journal of Railway Transportation and Technology, 2023)
The buffer stop also offers a gradual deceleration to the train, lowering the chance of passenger harm and railway damage. The buffer stop's conduct is critical for the train system's safety and integrity. The researcher conducted an analysis of the behavior of the buffer stop after being hit by an oncoming train and experienced failure in braking by using solid steel materials and with an additional layer of rubber on the head end of the train stop buffer. With reference to the impact force parameters that have been calculated in previous studies so that it can be viewed from the stress that occurs and the value of the lateral movement that occurs at the buffer stops.From the results of the analysis of this study it is known that an increase in the ability of the buffer stops by replacing steel material with rubber does not provide a significant increase, however, thickening the flange and web of the buffer stops provides a significant increase in capability with a ratio of 3,582 to the applied stress. and increased ability to reduce the length of the drift by a ratio of 2,478.